Happiness level among medical students of a medical college - Kulkarni, Surendra; Sanjeev, Chincholikar (International Journal Of Community Medicine And Public Health, 2019)
Background: In psychology, happiness is recognized as “emotion”. Emotion is divided into “negative emotion” and “positive emotion”. Psychologists believe that three main components of happiness are as follows: The relative existence of positive emotion, the lack of negative emotions and life satisfaction. Medical field is one of the fields that due to the clinical period and the pressures of hospitals and stressful environment have considerable effects on happiness and their job performance. Medical students are the future healers of the society. Happiness level of the students has effects on their performance. Hence the present study is an attempt to assess the happiness level of medical students. Methods: A cross-sectional study was carried out among medical students of a private medical college in Maharashtra. The participants in the study were medical students of all academic years enrolled in a private medical college. Happiness was measured by using Oxford Happiness Questionnaire. Results: It can be observed that happiness level of medical students is 70%. Female students are slightly more happy than male students. It was found that 49% study participants are unhappy as they are having insufficient pocket money. Conclusions: The level of happiness among students does not depend on their number of attempts in previous examinations. It was evident that percentage of happiness is much more in students living with their family. It was also observed Percentage of happiness is much more in students having some hobby. The study also revealed that level of happiness decreases marginally as the academic year progresses.